Implementasi Program Penataan Administrasi Kependudukan Di Kabupaten Madiun - Bagus Gempar Santosa (Jurnal Administrasi Publik, 2016)
Abstract: Population Administration Management Program in Madiun Regency (Study in the Department of Population and Civil Registration, Madiun Regency). To reach the goals of development population need a valid and accurate population data and setting of comprehensive population data. To get an accurate an invalid data, depatement of population and civil registration, Madiun regency should make policy by the Implementation of Population Administration Management Program in Madiun Regency. The study showed there are 4 (four strategic objectives) in the implementation of population administration management program by means of 15 (fifteen) indicator activities to be implemented. Than the 15 (fifteen) activities are connected with the implementation concept by George C. Edward III. the four variable point are Communication Aspect, Resources Aspect, Authorizing Signature Aspect, Bureaucracy Structural Aspect. On the other hand, there are also several supporting and inhibit factors in the implementation of this program. The factors supporting the implementation of this program such as the existence of a clear legal basis, the existence of clear communication between the actors and their supporting resources. On the other hand, there are also several factors that inhibit the implementation of this program such as the lack of facilities and infrastructures, the lack of public awareness about the ownership of personal documents, and the geographic location of Madiun regency which consist of forests and mountains. Keywords: Implementation, Population administration, Program Abstrak: Program Penataan Administrasi Kependudukan di Kabupaten Madiun (studi pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Madiun). Dalam mencapai tujuan pembangunan berwawasan kependudukan dibutuhkan data kependudukan yang valid dan akurat serta dibutuhkan pengaturan data kependudukan yang bersifat komperhensif. Untuk mendapatkan data yang valid dan akurat, Dinas Kependudukan dan Pencatatan Sipil Kabupaten Madiun membuat kebijakan dengan melaksanakan Program Penataan Administrasi Kependudukan di Kabupaten Madiun. Dari hasil penelitian ini, terdapat 4 sasaran strategis dalam Program Penataan Administrasi Kependudukan yang diimplementasikan dalam 15 kegiatan melalui indikator kerja. Kemudian dari 15 kegiatan tersebut dikaitkan dengan dengan konsep model implementasi George C. Edward III yang mengacu kepada empat variabel yaitu Aspek Komunikasi, Aspek Sumber Daya, Aspek Disposisi, dan Aspek Struktur Birokrasi. Selanjutnya terdapat beberapa faktor pendukung dan penghambat dalam implementasi Program Penataan Administrasi Kependudukan di Kabupaten Madiun. faktor pendukung yaitu adanya landasan hukum yang jelas, adanya komunikasi antar aktor yang jelas, dan adanya sumber daya pendukung. Sedangkan faktor penghambat yaitu sarana dan prasarana kantor yang kurang memadai, kurangnya kesadaran masyarakat tentang kepemilikan dokumen kependudukan, dan letak geografis Kabupaten Madiun yang terdiri dari hutan dan pegunungan. Kata Kunci: Implementasi, Administrasi Kependudukan, Program.